Antibacterial invitroand antidiarrhea invivoeffects of the infusion of sago roots (Metroxylon sagu) - Mohammad Bakhriansyah; Aswin Febria; Defiyanti Rahmah (Indonesian Journal of Pharmacy, 2011)
Fresh  root  of  sago  (Metroxylon  sagu)  traditionally  has  been  used  as  an antidiarrhea  in  South  Kalimantan  community.  However,  there  is  no  scientific data  yet  to  support  it.  The  aims  of  this  study  were  to  investigate  the antibacterial effect of the infusion of sago root on Salmonella typhi(S. typhi) as one  of  bacteria  causing  diarrhea in  vitro and  to  find  out  its  effects  as  anti diarrhea  in  male  mice  induced  by  castor  oil in  vivo. This  experimental  study measured the inhibitory zone in S. typhiculture and to count the frequency and duration  of  diarrhea.  It  used  3  concentrations,  i.e  10%;  20%  and  40%  of  the infusion of sago root. Chloramphenicol and aquadest were used as positive and negative  control  groups  respectively  in in  vitro study,  whereas  in  in  vivo one loperamide was positive control group. Chloramphenicol was used since it is an antibiotic  standard  for  eradicating S.  thypi, whereas  Loperamide  is  anti peristaltic  agent  from  declining  the  frequency  and  duration  of  diarrhea.  The infusion  inhibited  radical  zone  of  S.  typhi culture  by  7.8;  9.8  and  10  mm, decreased  the  frequency  of  diarrhea  24.23%;  40.54%  and  16.22%  and decreased  the  duration  of  diarrhea  26.69%;  52.92%  and  10.27%  at concentration  10%,  20%  and  40%,  respectively. As  conclusion  the  infusion  of sago  root  has  the  potency  as  anti  bacteria  and  decrease  the  frequency  and duration of diarrhea. The best concentration of the infusion of sago root is 20%.Key words: Metroxylon sagu, Mice, Anti diarrhea, Anti bacteria